Physicochemical Characteristics and Rheological Properties of Soymilk Fermented with Kefir - Egea, Mariana Buranelo; Santos, Daiane Costa Dos; Neves, Jordana Ferreira; Lamas, Isabelle Bueno; Filho, Josemar Gonçalves de Oliveira [UNESP]; Takeuchi, Katiuchia Pereira (AMG Transcend Association, 2023)
The objective of this work was to evaluate the physicochemical characteristics and rheological behavior of soymilk fermented with kefir. The titratable acidity ranged from 0.25 to 1.47 %; the pH ranged from 5.06 to 5.89 %. The soluble solids (SS) ranged from 1.82 to 5.38 Brix, while the differences between initial SS and final SS were 0.74 to 7.65 °Brix. The sedimentation percentage of the formulations ranged from 50.15 to 99.40 %. The rheological parameters for the flow behavior of the soymilk fermented with kefir were adjusted by the Herschel-Bulkley model. The 9 assays were characterized as non-Newtonian fluids because the behavior showed no linear relationship between the shear rate and shear stress. In the present work, the beverages were characterized as pseudoplastic fluids. In this work, we carry out the fermentation of soymilk with kefir without using any additional ingredients. The optimal treatment was determined, being a solution with an initial soymilk concentration of 5 g of kefir biomass (-0.5), 8 h (-1) of fermentation time, and 10 Brix of SS (+1).
Keywords: beverage; shear stress; soybean; viscosity